An observation of a potential metastatic mimic in bone marrow aspirate smears. (30th June 2021) - Gouda, Prabhu; Mazumder, Sujaya; Anbalagan, Anandhi; Kar, Rakhee
Abstract: We present an interesting observation of crushed erythroid precursors in bone marrow aspirate smears mimicking metastatic deposits. These artefactual clusters could be due to anticoagulation with ethylenediaminetetraacetic and also due to shearing forces exerted on the cells during aspiration and smearing. It is important to be aware of this potential mimic as in a given clinical context it can get misdiagnosed as metastasis.